Effects of promotion element on sales - Murithi Morris Murianki; Murithi Morris Murianki (Meru: Murithi Morris Murianki, 2014)
As firm increase in number, modern marketing calls for more than just producing the products, pricing them and making them accessible to the target market, in addition, they must also communicate to present and potential consumers and general public. The Marketing communication mix consists of five major modes of communication: advertising, sales promotion,public relations and publicity, personal selling and direct marketing. The objective of this study was to evaluate the effects of promotion on sales of agriculture of agricultural products produced by women groups. The population on sales of agricultural products by women groups.The population of the study comprised of 100 women groups registered with the Ministry of Sports, culture and social services by December 2012 in Imenti north district engaging in agricultural activities to generate income . simple random sampling technique was used to determine the sample size of 79. One official from each of these groups was picked as the respondent. Primary data was collected using personally administered structured questionnaires. Data was presented by use of frequency tables then analyzed using descriptive statistical techniques such as frequencies and percentages.Chi Square test was used to test the hypotheses. Personal selling is the promotion method widely used where they largely target women. The elements that were found to have influence on sales were advertised, sales promotion, personal selling and direct marketing. However public relations and publicity had no influence on sales of agricultural products produced by women groups.
A Research submitted in the partial fulfillment of the requirements for the degree of masters of business administration in the school of business and economics of Meru University of Science and Technology.